SeqMatcher: efficient genome sequence matching with AVX-512 extensions - Espinosa, Elena; Quislant-del-Barrio, Ricardo; Larrosa-Jiménez, Rafael; Plata-González, Óscar Guillermo (Springer Nature, 2024)
The recent emergence of long-read sequencing technologies has enabled substan- tial improvements in accuracy and reduced computational costs. Nonetheless, pair- wise sequence alignment remains a time-consuming step in common bioinformat- ics pipelines, becoming a bottleneck in de novo whole-genome assembly. Speeding up this step requires heuristics and the development of memory-frugal and efficient implementations. A promising candidate for all of the above is Myers’ algorithm. However, the state-of-the-art implementations face scalability challenges when deal- ing with longer reads and large datasets. To address these challenges, we propose SeqMatcher, a fast and memory-frugal genomics sequence aligner. By leveraging the long registers of AVX-512, SeqMatcher reduces the data movement and memory footprint. In a comprehensive performance evaluation, SeqMatcher achieves speed- ups of up to 12.32x for the unbanded version and 26.70x for the banded version compared to the non-vectorized implementation, along with energy footprint reduc- tions of up to 2.59x. It also outperforms state-of-the-art implementations by factors of up to 29.21x, 17.56x, 13.47x, 9.12x, and 8.81x compared to Edlib, WFA2-lib, SeqAn, BSAlign, and QuickEd, while improving energy consumption with reduc- tions of up to 6.78x
Keywords: Algoritmos computacionales; Arquitectura de ordenadores; Approximate string matching; AVX-512; Genome assembly; Hyyrö algorithm; Myers algorithm; SIMD